3D Selenium Sulfide@Carbon Nanotube Array as Long‐Life and High‐Rate Cathode Material for Lithium Storage. (6th September 2018) - Fan, Hai‐Ning; Chen, Shan‐Liang; Chen, Xiao‐Hua; Tang, Qun‐Li; Hu, Ai‐Ping; Luo, Wen‐Bin; Liu, Hua‐Kun; Dou, Shi‐Xue
Abstract: A 3D selenium sulfide@carbon nanotube array is designed and synthesized by encapsulating and anchoring a large amount of selenium sulfide (Se x S8− x ) into boron‐ and nitrogen‐codoped vertically aligned carbon nanotubes. Successfully employed as cathode material for the lithium metal battery, it exhibits long cycling lifetime and high rate capability with high energy density. Vertically aligned carbon nanotubes can not only enable fast migration to realize excellent rate capability and efficient utilization of the Se x S8− x loaded inside, but also provide optimal unidirectional void space to significantly reduce volumetric expansion and the polysulfide shuttling phenomenon during the cycling process. Meanwhile, the graphene layers decorated by element doping and held together by COOH‐ and OH‐enriched poly(acrylic acid) binder can efficiently consolidate Se x S8− x molecules inside the carbon nanotubes and prevent the separation of the active materials from the current collector during long‐term cycling. Benefiting from these features, the composite presents optimal cycling performance with a high initial Coulombic efficiency of 96% and a high reversible capacity of 818 mAh g −1 after 500 cycles at a current density of 500 mA g −1 . This composite thus represents one of the most promising cathode materials that can give the lithium metal battery long cycle life and remarkable power density. Abstract : A 3D selenium sulfide@carbon nanotube array is designed and synthesized by encapsulating and anchoring a large amount of selenium sulfide (Se x S8− x ) into boron‐ and nitrogen‐codoped vertically aligned carbon nanotubes. This architecture caters to practical application with a satisfactory rate capability and long lifespan by allievating volumetric change during the full lithiation process and enhancing the electric conductivity of intermediate product.